TRANSFORMASI PENGELOLAAN ARSIP SEKOLAH BERBASIS DIGITAL UNTUK MENINGKATKAN KOMPETENSI TENAGA ADMINISTRASI SEKOLAH - Raden Bambang Sumarsono; Agus Timan; Desi Eri Kusumaningrum; Dedi Prestiadi; Endra Ubaidillah; Wildan Darma Setiawan; Anita Dwi Nirmalasari; Siti Hamidah (LPPM Universitas Abdurrab, 2026)
Archive management in elementary schools is still dominated by manual methods, which pose risks of inefficiency, document loss, and low traceability. This community service activity aims to enhance the competence of School Administrative Staff (TAS) in Elementary Schools (SD) across the Sukun District, Malang City, through the transformation of digital-based archive management. The methods employed included lectures, brainstorming, hands-on practice (learning by doing) using the System Tracking Archive Responsive (STAR) application, simulations, mentoring, as well as pre-test and post-test evaluations via Google Forms. The training spanned a total of 32 lesson hours, involving 70 participants, and commenced with partner coordination, followed by core activities including: material delivery, system development practice, follow-up actions, and the signing of a Memorandum of Understanding (MoU). The results of the community service demonstrated a significant increase in competence: the average score rose from 81.30 (SD 6.86) in the pre-test to 87.56 (SD 8.50) in the post-test, with 38.57% of participants achieving the